Analysis of Apartment Rental Price Adequateness Across Prague Districts - Pulcová, Eliška; Janíčko, Martin, 1983-; Lichard, Tomáš; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2021)
The aim of the thesis is to develop a pricing model from where the author can derive whether the price per square meter of rental apartments is below or above the average market price per square meter of rental apartments in Prague per cadastral municipality, where possible. Author expects that price per month will be higher the closer to the center of Prague is the rental apartment located. This hypothesis is confirmed by all of the performed regression analysis that takes into account dummy variables controlling for location.
Vedoucí práce: Martin Janíčko
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2021
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2021
Způsob přístupu: Internet
Keywords: ekonomická analýza [obor dipl. práce]; diplomové práce; master's theses